2017
DOI: 10.1021/jacs.7b05404
|View full text |Cite
|
Sign up to set email alerts
|

Surface Inclusion of Unidirectional Molecular Motors in Hexagonal Tris(o-phenylene)cyclotriphosphazene

Abstract: A new unidirectional light-driven molecular motor suitable for host-guest surface inclusion complexes with tris(o-phenylene)cyclotriphosphazene (TPP) was synthesized. The motor molecules formed regular two-dimensional trigonal arrays covering the large facets of disc-shaped TPP nanocrystals. Photochemical and thermal isomerization studies demonstrated that the light-driven rotation of the anchored motors is similar to that observed in solution and is not compromised neither by either the surface confinement or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 67 publications
(104 reference statements)
2
82
0
Order By: Relevance
“…To the best of our knowledge, only one example by Feringa and Michl reports the inclusion of unidirectional light‐driven molecular motors in mesoporous materials made of a hexagonal tris( o ‐phenylene)cyclotriphosphazene (TPP) crystal host . X‐ray diffraction along with 31 P and 13 C solid‐state NMR experiments confirmed the formation of inclusion compounds, with motors standing on the facets of the disc‐shaped nanocrystals.…”
Section: Molecular Machines At Surfaces and Interfacesmentioning
confidence: 99%
“…To the best of our knowledge, only one example by Feringa and Michl reports the inclusion of unidirectional light‐driven molecular motors in mesoporous materials made of a hexagonal tris( o ‐phenylene)cyclotriphosphazene (TPP) crystal host . X‐ray diffraction along with 31 P and 13 C solid‐state NMR experiments confirmed the formation of inclusion compounds, with motors standing on the facets of the disc‐shaped nanocrystals.…”
Section: Molecular Machines At Surfaces and Interfacesmentioning
confidence: 99%
“…Several species evolved from the parent compound 1 have been developed and extensively investigated, and motors capable of rotating at room temperature with MHz frequencies upon visible light irradiation are now available. It was also shown that the light‐driven unidirectional rotation is preserved when the motors are deposited on macroscopic or nanostructured surfaces, embedded in membranes, and incorporated in soft or hard materials. Indeed, the robustness of the motor function is one of the main reasons for the widespread use of these compounds in the search for technological applications of artificial molecular machines.…”
Section: Basic Types Of Photochemically Driven Molecular Machinesmentioning
confidence: 99%
“…Recently, Feringa and coworkers designed a host–guest inclusion complex system comprising a light‐driven molecular motor and tris( o ‐phenylene)cyclotriphosphazene (TPP). In this system, the long shafts modified on the rotors provide recognition sites for host–guest interactions with disc‐shaped TPP crystals, leading to the coverage of their large facets with regular 2D trigonal arrays (Figure ).…”
Section: Microscale Applicationsmentioning
confidence: 99%
“…Schematic representation of self‐assembly between second‐generation molecular motors and TPP crystals. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Microscale Applicationsmentioning
confidence: 99%